A Methodological Quality Assessment of Meta‐Analyses on Sleep Disorder Treatments Using AMSTAR 2 - Leonard Ho; Yan Ling Kwok; Xi Chen; Irene X. Y. Wu; Chen Mao; Vincent Chi Ho Chung (Brain and Behavior)
ABSTRACT Background: Meta‐analyses (MAs) provide up‐to‐date, quantified evidence on treatment effects, which may be useful for clinical and policy decision‐making. However, the quality of MAs varies, and methodological flaws can limit their reliability. Aims: This review evaluated the methodological quality of MAs on sleep disorder treatments. Methods: We searched MEDLINE, EMBASE, and PsycINFO for eligible MAs on randomized controlled trials of sleep disorder treatments published between 2018 and 2023. We extracted MAs' bibliographical characteristics with a predesigned form and appraised their methodological quality using AMSTAR (A Measurement Tool to Assess Systematic Reviews) 2. We explored the associations between bibliographical characteristics and methodological quality ratings using Kruskal–Wallis tests and Spearman's rank correlation coefficients. Results/Outcomes: Among the 104 MAs, the majority (n = 82; 78.9%) had critically low quality, 19 (18.3%) had low quality, and only 3 (2.9%) had high quality. Regarding AMSTAR 2 critical domains, 97 (93.3%) MAs did not provide a list of excluded studies and justify the exclusions, 75 (72.1%) did not use a comprehensive literature search strategy, and 56 (53.9%) lacked a registered protocol and did not justify protocol deviations. Cochrane reviews (p = 0.018), MAs with European corresponding authors (p < 0.001), and MAs receiving European funding (p < 0.001) performed better than their counterparts. Conclusions/Interpretation: The methodological quality of recent MAs on sleep disorder treatments is unsatisfactory. Future reviewers should address the identified critical methodological issues. In addition, substantial resources and funding should be allocated to support training in evidence synthesis and critical appraisal for researchers and clinicians.